INFLATION SURGE OF 2021-2023 AND MONETARY POLICY IN EASTERN EUROPEAN COUNTRIES - Paslari, Andrei (Economy and Sociology, 2023)
This article provides an in-depth analysis of the current global economic landscape, with a particular focus on Moldova, Ukraine, Romania, and Poland. The scope of this article is to examine central banks’ responses to the challenges posed by 2021-2023 inflation. The research employs a combination of scientific methods, including empirical analysis and quantitative research. It utilizes data from reputable sources like the World Bank, National Banks, and National Bureaus of Statistics to examine various economic indicators. Statistical software R is used for data analysis, including Cross-Correlation Function (CCF) analysis. In response to rising inflation, Moldova and Ukraine raised interest rates significantly. Moldova later eased rates gradually, while Ukraine maintained a high rate to safeguard its currency. Romania and Poland, with stronger economies, saw milder rate hikes and less inflation increase compared to other Eastern European nations, adopting a cautious and delayed approach and still not reducing their base rates. A critical aspect of the research is the implementation of cross-correlation function (CCF) analysis, which is used to explore the time-lagged correlations between different economic variables, such as the Base policy rate, Commodity price index and IPC. The analyses conducted have revealed two significant patterns: a deficiency in the proactive adjustment of base rates by central banks in response to inflation and the lead-lag relationship between ascending commodity prices and inflation. These findings underscore the cautious approach taken by central banks and their delayed response to the impact of external factors on inflation dynamics.